2017
DOI: 10.1038/srep44951
|View full text |Cite
|
Sign up to set email alerts
|

Multiple H+ sensors mediate the extracellular acidification-induced [Ca2+]i elevation in cultured rat ventricular cardiomyocytes

Abstract: Acidosis has been known to cause “Ca2+ transients”, however, the mechanism is still uncertain. Here, we demonstrated that multiple H+ sensors, such as ASICs, TRPV1 and proton-sensing G protein coupled receptors (GPCRs) are involved in extracellular acidification-induced intracellular calcium ([Ca2+]i) elevation. By using calcium imaging measures, we observed that both ASIC and TRPV1 channels inhibitors suppressed the [Ca2+]i elevation induced by extracellular acidosis in cultured rat cardiac myocytes. Then, bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 39 publications
4
28
0
Order By: Relevance
“…TRPV1 expression in cardiomyocytes has been reported; however, its location and function in myocytes remain highly controversial. It has been reported to be in the cytosol, cell membrane, and mitochondrial membrane in different studies (5,15,17). Given this controversy, it is not clear whether the stress responses in our study were affected.…”
Section: H962 Trpv1 Depletion and Cardiac Stressmentioning
confidence: 63%
“…TRPV1 expression in cardiomyocytes has been reported; however, its location and function in myocytes remain highly controversial. It has been reported to be in the cytosol, cell membrane, and mitochondrial membrane in different studies (5,15,17). Given this controversy, it is not clear whether the stress responses in our study were affected.…”
Section: H962 Trpv1 Depletion and Cardiac Stressmentioning
confidence: 63%
“…Accumulating evidence demonstrated that ASICs participate in pathological progress of various organs such as brain, retinal, heart and articular cartilage ischaemic injuries. [17][18][19][20] ASIC1a a Ca 2+ -permeable ASICs subunit serve as novel targets for ischaemic stroke therapy. 8…”
Section: Discussionmentioning
confidence: 99%
“…Regarding endogenous acids, it should be remembered that cells use intracellular enzymes such as phospholipase C (PLC) and messengers such as inositol 1,4,5-trisphosphate (IP3) to increase the free Ca 2+ concentration in cytosol ([Ca 2+ ]c). PLC and other phospholipases are powerful acidifying enzymes, because one H + is released for each hydrolysed ester bond [47][48][49] . The hydrolysis of phospholipid esters and the generation of endogenous acids, such as arachidonic acid (AA), phosphatidic acid, and IP3, are at the base of the production of allergic mediators.…”
Section: Physio-pathological Effects Of Cellular Acidification In Epimentioning
confidence: 99%
“…The hydrolysis of phospholipid esters and the generation of endogenous acids, such as arachidonic acid (AA), phosphatidic acid, and IP3, are at the base of the production of allergic mediators. It is known that acidification can cause mobilization of the segregated Ca 2+ from intracellular stores 33,34,41,42,[50][51][52][53][54] , because protons can readily replace Ca 2+ in its ligand locations 48,55,56 . Moreover, it is known that the increase of [Ca 2+ ]c is involved in many physiological processes [57][58][59][60][61] but also in the triggering of pathological manifestations such as allergic responses 59 , airway hyper-responsiveness (AHR) 60 , and abnormal contraction and remodelling of airway smooth muscle (ASM) 61 .…”
Section: Physio-pathological Effects Of Cellular Acidification In Epimentioning
confidence: 99%
See 1 more Smart Citation